Comparison of Testosterone Undecanoate (TU) and Testosterone Enanthate (TE) with Combination of Depot Medroxyprogesterone Acetate (DMPA) on Spermatogenic Cells in Men - Retnaningtyas Siska Dianty; Yurnadi Hanafi Midoen (Journal of Biomedicine and Translational Research, 2022)
Introduction: Male hormonal contraception known as safe, effective, and reversiblecontraception. World Health Organization (WHO) multicentre study has been conducted aclinical study administrating of testosterone regimens and progestin to male with a remarkableresult. Azoospermia or severe oligozoospermia occurred in men with injection of TestosteroneEnanthate (TE) and Depot Medroxyprogesterone Acetate (DMPA) as well as TestosteroneUndecanoate (TU) and DMPA for a longer period. Decreasing gonadotropin as well astestosterone could lead to the amount of spermatogenic cells population declining by suppressingthe development of many kinds of cells. This narrative review was to compare howspermatogenic suppression in TE and TU with Combination of DMPA. Method: We arerandomly select article or journal from several databases and individual journal in certainkeywords. The keyword used were : (male hormonal contraception) OR (regimen testosterone))AND (progestin) OR (DMPA) OR (Testosterone enanthate) OR (Testosterone undecanoate) OR(male hormonal contraception combination)) AND (DMPA to spermatogenic cells) OR(Testosterone and DMPA to germ cell development)). After initial searching from databases andindividual journal website, 16 scientific articles or journals selected for the review. Result: Theresult indicated that injection of TE and DMPA had suppressed spermatogenesis, might notsuppressed sperm production for a longer period but the decreasing in type B spermatogoniauntil pachytene spermatocyte did occur. On the other hand, injection of TU and DMPA couldmaintain the suppression of sperm production for a longer period due to sustainable higher serumMPA with combination to even longer-acting TU would have more profound effect for that.Conclusion: It was known that combination of TU and DMPA might have better suppression onsperm production than TE and DMPA, otherwise further research needs to be obtained from thecombination of TU and DMPA on spermatogenic development and the association withintratesticular testosterone.